Isolated polydactyly of hands and feet in neonates: a case report - Pasha, Touheer; Afraneha; Ravanagomagan (International Journal of Research in Medical Sciences, 2025)
Polydactyly is a common congenital limb anomaly characterized by the presence of extra digits on the hands, feet, or both. When it occurs without any associated syndromic or systemic abnormalities, it is referred to as isolated polydactyly. In neonates, this condition presents with a wide spectrum of manifestations, ranging from small soft-tissue projections to fully developed digits containing bones and joints, and it may occur unilaterally or bilaterally. Classification is typically based on the anatomical location of the extra digit—preaxial (thumb or big toe side), postaxial (little finger or little toe side), or central—with postaxial polydactyly being the most frequently observed type, particularly among certain ethnic populations. Isolated polydactyly commonly follows an autosomal dominant pattern of inheritance with variable expression, although sporadic cases are also frequently reported. Accurate and early diagnosis is critical to differentiate isolated polydactyly from syndromic forms, as this distinction plays a key role in determining clinical management strategies and providing appropriate genetic counselling to families. In cases involving non-functional or minimally developed extra digits, intervention may not be necessary; however, surgical removal is often considered during infancy or early childhood for functional or cosmetic reasons, especially when the anomaly may interfere with hand or foot function or affect the child’s psychosocial development. This case emphasizes the clinical importance of recognizing isolated polydactyly in the neonatal period and underscores the need for thorough clinical evaluation, precise classification, and a coordinated, multidisciplinary management approach involving pediatricians, geneticists, and surgeons. Early intervention and counselling are essential for addressing parental concerns, guiding developmental support, and ultimately enhancing the quality of life and long-term functional outcomes for affected children.